ETHNOBOTANICAL STUDY OF MEDICINAL PLANTS IN MARIDAN VILLAGE, PANAJM PASER UTARA DISTRICT, EAST KALIMANTAN, INDONESIA - Ayu Winda Sari; Raflen Aril Gerungan (Universitas Negeri Manado, 2023)
Medicinal plants are generally very beneficial for treating various diseases or health problems. Knowledge about the use of medicinal plants is passed down orally from generation to generation. This research aims to determine the contribution of local knowledge about traditional medicinal plants in Maridan Village to treating certain diseases and the practice of using medicinal plants in Maridan Village. The results can provide information about the traditional medicinal uses of various local plants. Apart from that, it is also to increase public awareness to protect local biodiversity. The research results showed that the people of Maridan Village, Sepaku District, North Penajam Paser Regency, used 38 types of medicinal plants from 28 families. The part of the plant that is often used is the leaves; the processing that is often used is by boiling, and the method that is most often used is by drinking.